Profiling persons reported missing from hospitals versus mental health facilities. (December 2021) - Ferguson, Lorna
Missing person reports from hospitals and mental health facilities are a significant issue impacting patients, communities, and health and police sectors. Research on missing persons seldom considers the type of location from where people go missing, which can be troublesome due to the increased chances for experiencing harm during an episode from hospitals and mental health facilities. When location type is studied, these often remarkably different places are frequently blended together in analyses and discussions. This conflation has implications for research and the development of effective police preventive responses. To begin to address this gap, this study uses descriptive analysis and logistic regression to examine the descriptive and predictive profiles of those reported missing from hospitals versus those reported missing from mental health units. For this, data are taken from a sample of 916 closed missing person cases reported to a Canadian municipal police service over five years. Results suggest there are significant differences in both the descriptive and predictive profiles of individuals reported missing from these two location types, such as individuals with varying mental health and cognitive issues going missing from each place, respectively. Given the findings, the implications for research, policing, and risk management are discussed.